THE IMPORTANCE OF PUBLIC DEBATE IN DEMOCRATIC REGIMES - Sunay, Reyhan (European Scientific Journal, ESJ, 2012)
One of the most important problems facing democracies today is turning people into more active participants by involving them in the decision-making process. Public debate emerges as a significant tool in this process. Public debate is essentially a series of forums where people‟s opinions, interests and expectations are expressed on an issue that concerns the whole or part of the society. Active participation that will take place through such forums will be able to form a powerful ground for an understanding of efficient citizenship and a functioning democracy (powerful democracy). For, such forums are primarily those that bear the traces of how people wish to be governed in the context of preferences and expectations that have been voiced. Holding public debates on issues that concern society will also help creation of an open (transparent) and accountable administration. The risk of power abuse will be reduced to a minimum in an administration which is constantly supervised and held accountable through public debate. However, to fulfill all of these functions, existence of a society that consists of people that are tolerant and respectful of differences is required besides legal and constitutional guarantees that will enable free public debate.